Pengenalan Kegiatan Peregangan Tubuh Sebagai Aktivitas Fisik Dalam Menunjang Pembelajaran Efektif Siswa Sekolah Dasar - Dhito Dwi Pramardika; Meityn Disye Kasaluhe; Wendy Alexander Tanod; Ferdinand Gansalangi; Yana Sambeka; Eko Cahyono; Destu Ayu Hapsari (Poltekkes Kemenkes Surakarta, 2022)
Background: Teachers as educators have challenges in their student's learning during the transition from a pandemic to a COVID-19 endemic. Therefore, strategies and innovations are needed to improve effective education, especially in increasing concentration and body fitness. This is also a problem faced at SDN Inpres Enemawira, Tabukan Utara District, Sangihe Islands Regency. Based on this, the team aims to introduce body stretching training as a physical activity to support learning more effectively. Methods: This service uses an educational approach with 11 stages of health planning. The data collection technique is an observation method with a success indicator of 80% of students' ability in body stretching developing as expected. This program targets students in grades 4, 5, and 6, held on July 23, 2022, by the service team of the Nusa Utara State Polytechnic. Results: The results of this activity were as many as 18 students participated in the activity. Then the evaluation results showed that the completeness of 88.9% of participants had developed in following and repeating body stretching movements for three repetitions. Conclusion: The introduction of body stretching activities can support learning more effectively than before being introduced to body-trying activities. It can be seen by increasing students' concentration power and physical fitness.